Reflections on the current context and assessment of undergraduate medical education in Brazil - GERSON ALVES PEREIRA JÚNIOR; RAMIRO COLLEONI NETO; ROSANA ALVES; HERMILA TAVARES VILAR GUEDES; JORGE CARVALHO GUEDES; PEDRO TADAO HAMAMOTO FILHO; JOSÉ EDUARDO LUTAIF DOLCI; CESAR EDUARDO FERNANDES (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACT This reflection article can be divided into two complementary parts. The first shows the current context of medical education in Brazil, bringing the most recent data on the number of undergraduate students and its growing gap in relation to the reduced number of vacancies in medical residency, which, despite being the most appropriate modality to train specialists, has been overlooked by the excessive number of lato sensu graduate courses. The second part discusses the possibilities of evaluating medical training, which is terminal in Brazil, enabling the newly graduated physician to claim the professional registration and to practice medicine, being evaluated only by their own medical course. It also reviews the historical evolution and pros and cons of evaluating medical education for doctors trained both locally and abroad.